Aim high, hit ×10: psychological strategies driving the success of South Korean archers - Lee, Joonyoung; Hwang, Suyoung (Frontiers in Psychology, 2025)
Introduction: South Korean archers have excelled in global competitions. However, limited research exists on the factors contributing to their long-term success, particularly in the context of achieving ×10 scores. This qualitative study investigated the exceptional success of South Korean archers, focusing on their achievement of ×10 scores. Using a content analysis approach guided by epistemological perspectives, we examined the techniques, mental strategies, and coping skills for environmental factors influencing ×10 shooting performance Methods: Data were collected using convenience and snowball sampling from 65 Korean archers (Mage = 18 years ± 0.5; 55% female and 45% male) with experience hitting ×10 scores. A hybrid coding approach, combining deductive and inductive methods, was used to analyze responses. Deductive analysis applied an 8-step archery model, while inductive coding identified emergent themes. Trustworthiness was ensured through multiple rounds of coding, expert validation, and member checking. Results: The findings revealed several key themes across four phases of archery performance. In the preparation phase, confidence and positive mindset (30.9%), loss of self-consciousness (21%), mastery-oriented goals (18.5%), performance-oriented goals (18.5%), and psychological regulation strategies (11.1%) were significant. During the drawing and anchoring stages, physical techniques and stability (55.4%), surrounding environments (35%), and attentional focus (9.6%) were crucial. In the aiming and release phase, wind management strategies (48.4%), natural posture and kinesthetic balance (35.7%), and confidence and positive outcome expectation (15.9%) were prominent. Lastly, in the post-shot phase, positive emotion elevation (74%), cognitive affirmation (14%), and tension management (12%) were key themes. These themes illustrate the comprehensive strategies, techniques, and coping skills essential for achieving ×10 scores in archery. Conclusions: The holistic approach equips Korean archers to manage psychological demands and maintain consistent performance under pressure. The findings provide practical applications for archers, coaches, and sport psychologists, guiding the development of interventions to enhance mental strategies, physical techniques, and environmental coping skills, thereby improving performance outcomes in archery sports.